Pricing Formation And Market Variability Characteristics In Walnut Cultivation And Its Delivery To Consumers - et. al., Abror Inobatov Boshlarovich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, the authors describe the features of growing walnuts in Uzbekistan, the sale of grown products in terms of economic efficiency. It was noted that the cultivation of walnuts in small-scale farms does not allow to ensure the quality of the product, the inability to follow the agronomic techniques of walnut tree care leads to a decrease in product quality. Based on the results of the analysis and research, conclusions were developed and recommendations for the development of the yoghurt coconut business were included in the article.